2021
DOI: 10.3390/nu13020700
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Risk of Dementia and Alzheimer’s Disease in the EPIC-Spain Dementia Cohort Study

Abstract: The Mediterranean diet (MD) has shown to reduce the occurrence of several chronic diseases. To evaluate its potential protective role on dementia incidence we studied 16,160 healthy participants from the European Prospective Investigation into Cancer and Nutrition (EPIC)-Spain Dementia Cohort study recruited between 1992–1996 and followed up for a mean (±SD) of 21.6 (±3.4) years. A total of 459 incident cases of dementia were ascertained through expert revision of medical records. Data on habitual diet was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 46 publications
0
39
0
2
Order By: Relevance
“…Epidemiological findings are consistent in showing that adherence to a Mediterranean diet characterized by high intake of fruit, vegetables, cereals, and legumes, and low intake of meat, high-fat dairy, and sweets, is consistently associated with a lower risk of AD (Yusufov et al, 2017). In a Mediterranean study involving over 16,000 middle-aged and elderly participants followed up for over 20 years, Andreu-Reinón et al (2021) found that adherence to the MedDiet was associated with a 20% lower risk of AD overall in the EPIC-Spain Dementia Cohort. Adherence to the MedDiet increases the diversity of microbiota after 1 year of intervention, with higher ratio of Firmicutes/Bacteroidetes and higher levels of SCFAs, which is negatively associated with inflammatory markers.…”
Section: Diet-based Microbiota Modulationmentioning
confidence: 78%
“…Epidemiological findings are consistent in showing that adherence to a Mediterranean diet characterized by high intake of fruit, vegetables, cereals, and legumes, and low intake of meat, high-fat dairy, and sweets, is consistently associated with a lower risk of AD (Yusufov et al, 2017). In a Mediterranean study involving over 16,000 middle-aged and elderly participants followed up for over 20 years, Andreu-Reinón et al (2021) found that adherence to the MedDiet was associated with a 20% lower risk of AD overall in the EPIC-Spain Dementia Cohort. Adherence to the MedDiet increases the diversity of microbiota after 1 year of intervention, with higher ratio of Firmicutes/Bacteroidetes and higher levels of SCFAs, which is negatively associated with inflammatory markers.…”
Section: Diet-based Microbiota Modulationmentioning
confidence: 78%
“…Moreover, legumes and vegetal oils could improve insulin sensitivity, which could, in turn, influence cognitive function ( 34 ). Indeed, in the EPIC-Spain Dementia Cohort, a recent investigation observed that a high rMED adherence score was associated with a 20% lower risk of dementia ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from large-scale cohort studies and long-term intervention trials support the protective effect of this pattern against several neurodegenerative disorders [74]. Among the largest prospective observational studies are the Singapore Chinese Health Study (16,948 men and women followed for an average of 20 years) [75], the European Prospective Investigation into Cancer and Nutrition (EPIC-Norfolk, 8009 older individuals with an average of 13 years of follow-up) [76], the EPIC-Spain study (16,169 adults followed for approximately 22 years) [77] and the Coronary Artery Risk Development in Young Adults (CARDIA, with follow-up for up to 20 years) [78]. These studies found that higher adherence to a Mediterranean diet was associated with a significantly lower risk of developing all-cause dementia, AD or mild cognitive impairment.…”
Section: Mediterranean-type Dietary Patternmentioning
confidence: 97%